'Our Whole History has been Ruined!' The 1981 Hunger Strike and the Politics of Republican Commemoration and Memory*. Issue 1 (2nd January 2016) - Hopkins, Stephen
Abstract: This article will analyse the contested and complex commemorative politics associated with the Irish republican hunger strikes of 1980–1981, and the struggle over their legacies during the course of the last 40 years, and the last decade in particular. This contest has been framed not simply by the expected disputes between the republican narrative and those memories associated with the Protestant/unionist/loyalist communities or the 'official' interpretation of the British state. For many years, the broad republican 'family' could commemorate and celebrate the self-sacrifice and martyrdom of the hunger strikers as a foundational and unifying narrative for the movement. The first section of the article will establish the central significance of the commemoration of these events for Irish republicanism's sense of continuity with past incarnations of the movement. The second section will analyse the politics of memory in the contemporary, post-Good Friday Agreement Republican commemorative landscape. This landscape is no longer pristine and uncomplicated. In 2005, the former Public relations officer for the IRA prisoners in the Maze/Long Kesh prison, Richard O'Rawe, alleged in his book Blanketmen, that the hunger strike had been prolonged by the Provisional IRA leadership outside the jail for political gains. These claims have triggered a long-running and ongoing dispute between erstwhile comrades. All sides in the contemporary political conflict within republicanism have attempted to recruit the historical and mythical 'symbolic capital' of the hunger strikers to their respective causes. This has seen the practices of commemoration become weapons in the battle over the past of the movement, but also over the current and future trajectory of Irish republicanism. The article will argue that conflict over the commemoration of the hunger strikes is now one of the most visible and important dimensions of the fragmented character of the republican family, and represents a crucial component in the contemporary politics of Irish republican memory.